Receptivity to feedback: an investigation of the influence of feedback sign, feedback specificity, and goal orientation - Waples, Christopher J. (Kansas State University, 2015)
This study was designed to examine the combined influence of feedback sign (i.e., positive or negative), feedback specificity, and goal orientation on individuals’ receptivity to performance feedback. Performance feedback is an often-prescribed solution to performance problems for both individuals and organizations, but evidence regarding its effectiveness as a mechanism for promoting positive outcomes has been mixed. It has been argued that one reason for the inconsistency in previous research findings may be a failure to adequately account for reactions to feedback (e.g., receptivity). Accordingly, this study focused on a series of variables with the potential to influence receptivity, in pursuit of a more comprehensive understanding of the feedback process. It was expected that individuals with certain achievement goal orientations would be more or less receptive to different characteristics of the feedback itself, and that the nature of the task being performed would further influence their willingness to accept feedback and implement task-relevant behavioral changes. Data were collected from 536 participants via Amazon’s Mechanical Turk marketplace. Participants completed the experiment in an online environment. Each participant was asked to complete a pair of error-detection tasks, focused on either mathematical computations or grammatical accuracy. Conditionally-assigned, fabricated feedback was provided after task performance on the initial trial. Surveys were used to assess goal orientation and feedback receptivity. Results indicated that greater feedback specificity was associated with greater receptivity to feedback. Analysis also revealed that feedback sign, feedback specificity, and goal orientation interact to influence receptivity, such that for performance-oriented individuals, specific positive feedback leads to the highest levels of receptivity and specific negative feedback prompts the lowest levels of receptivity. For mastery-oriented participants, however, specific feedback was associated with high levels of receptivity, regardless of whether that feedback was positive or negative. The results are discussed within the context of relative theoretical perspectives. Practical implications, promising avenues of future inquiry, and strengths and limitations of the research are discussed.
Keywords: Receptivity to feedback; Feedback sign; Feedback specificity; Goal orientation; Performance feedback; Psychology (0621)